MUCOLYTIC THERAPY IN PEDIATRICS: MYTHS AND REALITY - O.I. Simonova (Union of pediatricians of Russia, 2009)
The article highlights the treatment of the respiratory tract diseases accompanied by the development of mucostasis and dyscrinia among children. The author described the mucolytic therapy thoroughly by the original medication from the N_acetylcysteine group, which has both mucolytic and antioxidant and antiinflammatory effects. These properties are more important in the event of the chronic bronchopul-monary pathology and explain its high efficiency. Different dosage forms allow the doctor to apply a medication among patients of various age, including neonates and infants.Key words: respiratory tract diseases, mucostasis, dyscrinia, mucolytic therapy, children.